2018
DOI: 10.1111/jep.12897
|View full text |Cite
|
Sign up to set email alerts
|

Developing Student Evidence‐Based Practice Questionnaire (S‐EBPQ) for undergraduate nursing students: Reliability and validity of a Chinese adaptation

Abstract: The newly cross-culturally adapted S-EBPQ possesses adequate validity, test-retest reliability, and internal consistency and therefore may be utilized in nursing education to assess EBP of undergraduate nursing students in Mainland China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 30 publications
4
6
1
Order By: Relevance
“…Although the revised model exhibited a better fit, the CFA indices indicated that the 4-factor structure did not fit well with the data. This result differed from the findings of previous studies in Australia and China in that the fit indices indicated that the four factors fit the data well [11,12]. Such differences may be due to the sample characteristics with different educational backgrounds.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Although the revised model exhibited a better fit, the CFA indices indicated that the 4-factor structure did not fit well with the data. This result differed from the findings of previous studies in Australia and China in that the fit indices indicated that the four factors fit the data well [11,12]. Such differences may be due to the sample characteristics with different educational backgrounds.…”
Section: Discussioncontrasting
confidence: 99%
“…It was consistent with those of the original S-EBPQ and previous studies [10e13]. The explanatory power of the 4-factor model was 66.26%, which was similar to the findings in previous studies [12,13]. In addition, there was no cross-loaded item.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations